2020
DOI: 10.21203/rs.3.rs-58871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Job Satisfaction and Associated Factors Among Midwives Working in Health Centers of Central Zone, Ethiopia

Abstract: Background: Job satisfaction depends on the interactions of employee’s personal characteristics, values and expectations with the work environment and the organization. Low job satisfaction among midwives is supposed to be a problem to achieve organizational goals. Due to this reason, it is a must to determine their level of satisfaction and the contributing factors. The objective is to assess job satisfaction and associated factors among midwives working in Health Centers of Central Zone of Tigray, Ethiopia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Thirty-four articles 2,12,13,1534,4152 were used to compute the pooled prevalence of health professionals’ job satisfaction. It was found that 46.68% (95%, CI: 41.82, 51.54) of health professionals had satisfaction in their job with a remarkable heterogeneity among the included studies ( I 2 = 95.8%, P < .01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four articles 2,12,13,1534,4152 were used to compute the pooled prevalence of health professionals’ job satisfaction. It was found that 46.68% (95%, CI: 41.82, 51.54) of health professionals had satisfaction in their job with a remarkable heterogeneity among the included studies ( I 2 = 95.8%, P < .01).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were excluded due to different outcomes. Finally, 35 articles 2,12,13,1534,4152 were included in the final analysis of the current systematic review and meta-analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest prevalence of job satisfaction was reported on study done in Mekelle city (67.3%) [62] and the least was in Amhara region (31.7%) [33]. Regarding to profession, 14 (46.7%) were conducted by including all health professionals [16, 33, 63, 65, 66, 68-70, 72, 74-78] and 4 on anaesthesia and midwiferies; 2 for each [61,64,68,71] (Table 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Four full‐text articles were redundant, one full‐text article was out of Ethiopia, and one full‐text article was out of recommended date and excluded. Finally, we end up with 40 full‐text articles [39–77] for systematic review and meta‐analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%